Analisis Product Quality, Price dan Sertifikasi Halal terhadap Keputusan Pembelian Produk Kecap Manis Cap Nasional - Zaki Mubarak; Rizka Amalia; Lisda Aisyah (ISLAMIC BUSINESS and FINANCE, 2023)
The background of this research is that it is currently known that “Nasional” brand Soy Sauce is not very well known and we rarely find promotions through television media, but the level of sales of Nasional soy sauce in second place after ABC soy sauce, thus making researchers interested in conducting research and proving what factors influence the buyer's decision by using several variables, that is product quality, price, and halal labeling. This type of research is survey research and uses a quantitative approach with data collection methods: observation, questionnaire, and documentation. While data collection techniques used are primary data and secondary data. The results of the study indicate that the product quality variable, the price, and the halal labeling are able to explain the purchasing decisions variable of 52.1% and the remaining 47.9% explained by other variables outside the research. Partially, the product quality variable (X1) does not affect purchasing decisions. The price (X2) and the halal labeling variables (X3) have an effect on purchasing decisions. Meanwhile, simultaneously, the product quality (X1), the price (X2), and the halal labeling variables (X3) haveas an effect on the purchasing decisions.Keywords: Product Quality, Price, Halal Labeling, Purchasing Decisions.